Sex differences in the kinematics and neuromuscular control of landing: Biological, environmental and sociocultural factors - Bruton. M. R.; O`Dwyer, N.; Adams, R. (Journal of Electromyography and Kinesiology, 2013)
Potential sex differences in patterns of movement of recreational and competitive athletes were investigated in a systematic review of lower limb kinematics, muscle activation and stiffness during landing and hopping tasks. Little support for sex-specific lower limb kinematic patterns was found in 17 studies retrieved on landing and hopping. Ten studies retrieved on muscle activation during landing provided no support for sex-specific patterns. Four articles retrieved on leg stiffness established that absolute stiffness was lower in females, but differences in stiffness normalized to body mass were less clear. The wider literature indicates that a combination of biological, environmental and sociocultural constraints may shape movement patterns differently in females and males. Sociocultural factors differentially affect accumulated motor experience, practice opportunities and focus of attention in females, leading to differences in motor skill that confound the comparison of female and male movements. The findings of the review support the hypothesis that such sex differences in athletic performance are likely to diminish or disappear with increasing skill. In everyday movement tasks, however, where level of skill is a less meaningful dimension than in sport, differences in movement patterns observed between females and males point instead to the influence of subtle societal expectations on movement patterns.